2019
DOI: 10.1101/762294
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sporadic ERK pulses drive non-genetic resistance in drug-adapted BRAFV600Emelanoma cells

Abstract: Anti-cancer drugs commonly target signal transduction proteins activated by mutation. In patients with BRAF V600E melanoma, small molecule RAF and MEK kinase inhibitors cause dramatic but often transient tumor regression. Emerging evidence suggests that cancer cells adapting by non-genetic mechanisms constitute a reservoir for the development of drug-resistant tumors. Here, we show that few hours after exposure to RAF/MEK inhibitors, BRAF V600E melanomas undergo adaptive changes involving disruption of negativ… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 67 publications
1
10
0
Order By: Relevance
“…We also observed that within individual clusters of closely related primed cells, not all cells contained higher levels of pERK, which may reflect pulsatile changes in pERK as documented elsewhere (Supp. Fig 8D) (Gerosa et al, 2019) . These results suggest that primed cells are able to maintain residual MAPK signaling following vemurafenib treatment that may allow them to continue proliferating in the face of drug.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…We also observed that within individual clusters of closely related primed cells, not all cells contained higher levels of pERK, which may reflect pulsatile changes in pERK as documented elsewhere (Supp. Fig 8D) (Gerosa et al, 2019) . These results suggest that primed cells are able to maintain residual MAPK signaling following vemurafenib treatment that may allow them to continue proliferating in the face of drug.…”
Section: Resultsmentioning
confidence: 96%
“…Shown is one such example. We speculate that this variability may be a result of pulsatile MAPK signaling, which has been documented in other melanoma cell lines (Gerosa et al 2019), and our snapshot measurement of ERK phosphorylation via immunofluorescence E. After identifying primed cells in situ, we performed both single-molecule RNA FISH and immunofluorescence to measure gene expression and phosphorylated ERK in the same single cells. Shown is the relationship between phosphorylated ERK levels and AXL (left) or SOX10 (right) expression in individual primed (green points) and non-primed (gray points) cells.…”
Section: Supplementary Figure 8 Primed Cells Giving Rise To Vemurafementioning
confidence: 89%
See 1 more Smart Citation
“…These include (i) the use of CRISPR-mediated tagging of endogenous effector proteins, such as AKT or FOXO, to follow their dynamic translocation live and without stoichiometric changes and (ii) the integration of quantitative, multiplexed immunofluorescence in time course studies that seek to assess a wider repertoire of signaling responses at the single-cell level (65)(66)(67). Proof-of-concept studies from Sorger and his team illustrate the detailed cell signaling insight that can be obtained with some of these approaches and the translational potential of the acquired knowledge (62,68). Adoption of these methodologies will likely be instrumental in closing the PI3K signaling knowledge gaps that will be discussed next.…”
Section: Technological Challenges and Potential Solutionsmentioning
confidence: 99%
“…Recent technological advances in high content imaging and -omics technologies are offering novel ways in which future studies may address the complexity of PI3K-mediated stemness, through a combination of conventional mechanistic studies and emerging systems biology strategies applied successfully in other areas [124][125][126][127]. To succeed in providing a unifying picture of PI3K-mediated stemness in development and cancer, such systems biology approaches will necessitate better interdisciplinary 'cross-talk' to combine the multifaceted mechanistic data on this pathway already available into comprehensive computational models.…”
Section: Future Directionsmentioning
confidence: 99%